Characteristics of Ischemic Stroke Patients With COVID-19 Based on Gender and Age at RSPAL Dr. Ramelan Surabaya From 2020 To 2022 - Loula Kamal; Ni Komang Sri Dewi Untari; Duti Sriwati Aziz; Asami Rietta Kumala (International Journal Labs, 2026)
Stroke is the second leading cause of death worldwide. Most strokes are ischemic, with varying incidence by age and gender. COVID-19 is known to increase the risk of acute ischemic stroke through inflammatory and hypercoagulable mechanisms. According to the WHO, COVID-19 patients have an estimated 5% risk of developing ischemic stroke. Previous research indicates that ischemic stroke associated with COVID-19 predominantly occurs in patients over 69 years of age and is more common in men. This study aimed to determine the characteristics of ischemic stroke patients associated with COVID-19 based on gender and age at Dr. Ramelan Naval Hospital, Surabaya, from 2020 to 2022. This descriptive study employed quantitative methods using secondary data derived from the medical records of patients who met the inclusion criteria. The study was conducted at Dr. Ramelan Naval Hospital, Surabaya, from March to September 2025. The results showed that, of the 86 cases, 90.7% of patients were identified as having risk factors for cardiovascular disease. Among patients with risk factors, males were more numerous (69%), with a predominance in the ?50-year age group (88%). However, among patients without risk factors, the numbers of males and females were relatively equal, with a similar predominance in the ?50-year age group (75%). The conclusion of this study is that ischemic stroke patients with COVID-19 at Dr. Ramelan Naval Hospital, Surabaya, between 2020 and 2022 were predominantly male and aged ?50 years.